Common ground: the opportunity of male contraceptives as MPTs - Vahdat, Heather L.; Nickels, Logan M. (Frontiers in Reproductive Health, 2023)
Multipurpose prevention technologies (MPTs) and male contraceptive methods are currently in development to address unique and critical needs facing the global reproductive health community. Currently, MPT products in development are exclusively female-focused due to the readily available nature and regulatory precedent offered by female contraceptive active pharmaceutical ingredients (APIs); however, the opportunity to explore codevelopment with male contraceptive methods, which are at a comparatively early stage of development, should not be overlooked. These fields face parallel challenges including research and development, commercialization, regulatory approval, and market uptake, and these parallels can inform strategic alignment between the fields. One challenge that precludes codevelopment, however, is the path to market and associated funding models for these innovative, yet underappreciated fields. Without candid review, reconsideration, prioritization, and innovation led by the donor and investment communities, product developers will have no compelling reason to consider accepting the added regulatory and fiscal burden associated with combining development streams.